2015
DOI: 10.1186/s12944-015-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training enhances the in vivo cholesterol trafficking from macrophages to the liver independently of changes in the expression of genes involved in lipid flux in macrophages and aorta

Abstract: BackgroundRegular exercise prevents and regresses atherosclerosis by improving lipid metabolism and antioxidant defenses. Exercise ameliorates the reverse cholesterol transport (RCT), an antiatherogenic system that drives cholesterol from arterial macrophages to the liver for excretion into bile and feces. In this study we analyzed the role of aerobic exercise on the in vivo RCT and expression of genes and proteins involved in lipid flux and inflammation in peritoneal macrophages, aortic arch and liver from wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
0
26
0
4
Order By: Relevance
“…Regular aerobic exercise increases Cyp7a1 levels, increases the effective control of cholesterol in the liver, and prevents atherosclerosis by increasing HDL levels. 42 PXR plays an important role in the regulation of CYP3A4, a major DME in humans. 43 In a previous study, swimming exercise for 8 weeks was found to increase mRNA and protein expression of PPAR in elderly mice, and the expression of 3-hydroxyacyl CoA dehydrogenase and carnitine palmitoyl transferase-I, target genes of PPAR, was also increased in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Regular aerobic exercise increases Cyp7a1 levels, increases the effective control of cholesterol in the liver, and prevents atherosclerosis by increasing HDL levels. 42 PXR plays an important role in the regulation of CYP3A4, a major DME in humans. 43 In a previous study, swimming exercise for 8 weeks was found to increase mRNA and protein expression of PPAR in elderly mice, and the expression of 3-hydroxyacyl CoA dehydrogenase and carnitine palmitoyl transferase-I, target genes of PPAR, was also increased in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…All of these improvements correlate with reduction in macrophages in the plaques, implying that exercise can prevent foam cell formation and reduced macrophage motility, the hallmarks of atherogenesis. Support for such a hypothesis comes from another recent report that indicated an exercise‐mediated enhancement in reverse cholesterol transport …”
Section: Role Of Exercisementioning
confidence: 98%
“…Support for such a hypothesis comes from another recent report that indicated an exercise-mediated enhancement in reverse cholesterol transport. 187 Exercise significantly reduced triglyceride levels, but its effects on cholesterol content vary. 179 Lowintensity exercise decreases total cholesterol content, but increases OxLDL, HDL, and LXR␣ (most likely through PPAR␥ ) levels, the latter two being involved with cholesterol efflux and thus having low propensity for atherosclerosis.…”
Section: Role Of Exercisementioning
confidence: 99%
See 2 more Smart Citations